y−5x6=−1y-5x6=-1 AA must be positive, so multiply both sides of the equation by −1-1 .−1⋅(y−5x6)=−1⋅−1-1⋅(y-5x6)=-1⋅-1 Simplify the left side of the equation.Tap for more steps...Multiply −1-1 by y−5x6y-5x6 to get −1(y−5x6)-1(y-5x6) .−1(y−5x6)=−1⋅−1-1(y-5x6)=-1⋅-1 Apply the distributive property.−1y−1(−5x6)=−1⋅−1-1y-1(-5x6)=-1⋅-1 Rewrite −1y-1y as −y-y .−y−1(−5x6)=−1⋅−1-y-1(-5x6)=-1⋅-1 Simplify −1(−5x6)-1(-5x6) .Tap for more steps...Multiply −1-1 by −1-1 to get 11 .−y+1(5x6)=−1⋅−1-y+1(5x6)=-1⋅-1 Multiply 5x65x6 by 11 to get 5x65x6 .−y+5x6=−1⋅−1-y+5x6=-1⋅-1 −y+5x6=−1⋅−1-y+5x6=-1⋅-1 Reorder −y-y and 5x65x6 .5x6−y=−1⋅−15x6-y=-1⋅-1 5x6−y=−1⋅−15x6-y=-1⋅-1 Multiply −1-1 by −1-1 to get 11 .5x6−y=15x6-y=1